Profiling of bushmeat value chain actors in the northern sector of Ghana for targeted interventions to reduce zoonotic disease and public health risks - Ouattara, Blaise; Akita, Cecilia; Kikimoto, Boi; Emikpe, Benjamin Obukowho; Asare, Derrick Adu; Takyi, Prince Nana; Shaban, Salisu; Kong, Jude Dzevela (Frontiers in Veterinary Science, 2026)
BackgroundThe bushmeat trade in Northern Ghana is important for rural economies and food security, but it faces challenges like poor hygiene, the risk of zoonotic diseases, and the fact that it is not sustainable. There is insufficient information regarding the principal actors, their socio-economic functions, and adherence to hygiene and food safety standards.MethodsA mixed-methods design was employed to gather data from 61 purposely selected participants involved in the bushmeat value chain in Ghana's Upper East and Upper West regions. The methods used to collect data included structured questionnaires, focus group discussions with hunters, traders, consumers, and wildlife officers, direct observations, and participatory techniques to find out how food is distributed and how safe it is to eat.ResultsThe study found that all the hunters were men between the ages of 25 and 50, with a majority lacking formal education (59.5%), who worked part-time mostly during the dry season and earned low monthly incomes, with over half making less than GHs100. Most of the hunters and traders had not been taught how to keep food safe. Almost all of the meat (97.3%) was processed in the bush using traditional smoking and then sold in dirty places. Seventy percent of trade was in smoked meat, and 58.8% of that was moved in baskets or bags. Hunters had low pay, a 95% drop in wildlife, and prices in the market that traders set.ConclusionNorthern Ghana's bushmeat trade is a multifaceted social, economic, and public health issue that requires targeted interventions to enhance sanitation, develop new revenue streams, and more effectively implement laws protecting wildlife. To effectively deal with these problems, all stakeholders, including local communities, government agencies, and NGOs, need to work together to find a sustainable balance between protecting biodiversity, public health, and the economic wellbeing of rural people.